Vertebral Bone Quality Score as a Predictor of Pedicle Screw Loosening Following Surgery for Degenerative Lumbar Disease - Li, Wenshuai; Zhu, Houze; Hua, Zijian; Miao, Dechao; Wang, Feng; Tong, Tong; Wang, Linfeng (Spine (Philadelphia, Pa. 1976), 2023)
Retrospective study. To investigate whether magnetic resonance imaging-based vertebral bone quality (VBQ) score can predict pedicle screw loosening in patients who underwent pedicle screw fixation, and to compare, which measurement, the VBQ score or the Hounsfield unit (HU) value, is more predictive of pedicle screw loosening. In clinical work, we found that patients with screw loosening had higher VBQ scores. In addition, some studies have found a correlation between VBQ scores and osteoporosis. Patients who were treated with lumbar pedicle screw fixation were reviewed. The VBQ score was measured using magnetic resonance imaging scans. The HU value for L1 to L4 lumbar bone mineral density was measured with computed tomography scans. Logistic regression analysis was used to identify factors associated with pedicle screw loosening. Receiver-operating characteristic curve analysis was used to evaluate the value of VBQ scores in predicting pedicle screw loosening. A total of 156 patients were included in the final analysis. The pedicle screw loosening rate was 35% (55 of 156 patients). The postoperative low-back pain visual analog scale score was higher in the loosening group (3.0 ± 2.0 vs . 2.4 ± 1.8; P < 0.05). The VBQ score was higher in the loosening group than in the nonloosening group (3.28 ± 0.58 vs . 2.82 ± 0.50; P < 0.01). In multivariable analysis, nonsingle segment fixation [odds ratio (OR): 3.992; 95% CI: 1.643-9.701; P = 0.002], lowest instrumented vertebrae at S1 (OR: 3.378; 95% CI: 1.387-8.226; P = 0.007), HU value (OR: 0.988; 95% CI: 0.976-1.000; P = 0.047), and VBQ score (OR: 3.908; 95% CI: 1.624-9.405; P = 0.002) were factors associated with screw loosening. The areas under the curve for using the VBQ score and HU value to predict pedicle screw loosening were 0.720 and 0.702, respectively. The optimal VBQ score threshold was 3.05 for predicting pedicle screw loosening (sensitivity: 0.655; specificity: 0.713). The VBQ score was an influential factor associated with lumbar pedicle screw loosening, and a higher VBQ score was significantly correlated with a higher risk of screw loosening. The VBQ score was a better predictor of pedicle screw loosening than the HU value in patients who underwent pedicle screw fixation for degenerative lumbar disease.